Redeeming loneliness : Paul Ricoeur’s strangeness and recognition in Marilynne Robinson’s Gilead, Home and Lila - Stimson, Amy (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2017.